PENGARUH KUALITAS LAYANAN DAN HARGA TERHADAP KEPUTUSAN PELANGGAN UNTUK MENGGUNAKAN JASA SALON BUNDA RIDA - Adriana, Fitri; Zainuddin, Muh Zabir; HM, Suyuti; Utha, Rasidin (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2022)
The Effect of Service Quality and Price on Customer's Decision to Use The Services of Bunda Rida Salon. Thesis, Management Study Program, Faculty of Economics and Business. Guide I: Mr. H.Muh.Zabir Zainuddin, and Mentor II: Mr. Suyuti HM. This research aims to find out the influence of service quality and price on customer decisions to use the services of Salon Bunda Rida. To achieve these goals, qualitative and quantitative data, data collection techniques are used with observations, interviews, and documentation. The population in this study is a customer of Salon Bunda Rida. The samples in this study used multivariate analysis (correlation or multiple regression), then the number of sample members was at least 10 times the variables studied (independent + dependent). In this study there are 2 independent variables and 1 dependent variable (there are 3 variables), then 3 x 10 = 30. So the number of samples in this study is as many as 30 respondents. . The data was collected through questionnaires and analyzed using multiple linear regression analyses and using hypothesis tests, i.e. partial t tests and simultaneous F tests. The results of the analysis showed that there was a significant and positive influence between the quality of service and price on the decisions of customers, both partially and simultaneously.